From Financialization to Low and Non-profit: emerging Media Alternatives for Freedom - Almiron-Roig, Nuria (2011)
"In the midst of what is probably the worst economic and financial crisis the capitalist world has ever experienced, professional journalistic structures and news organizations are disintegrating. While mainstream current economic and media gurus – and the whole media executive class around the globe – are clamouring for a business model change that allows them to go on making lots of money, many voices have been raised in unison to ask for a true radical change: the public interest should be the first goal, and not money. This paper presents the outcome of a research project on non-profit alternatives currently under debate, the aim of which is to help journalism survive." [Information des Anbieters]
https://katalog.adlr.link/Record/finc-80-15370